Pemekaran Nagari Duo Koto Kecamatan Tanjung Raya Kabupaten Agam Lahirnya: Nagari Koto Malintang 2005-2011 - Mayasari, Susi; Witrianto, Witrianto; Nurhuda, Ahmad (Pendidikan Sejarah, 2013)
ABSTRACT This thesis examines about the Redistricting Nagari Koto Duo, district Tanjung Raya of Agam ( Nagari Koto Malintang 2005-2011 was born ). Besides, it also examines how the impact of the expansion in the field of social, cultural, economic and political. Based on the above subject matter research problem formulated as follows: (1) How Redistricting Process Nagari Duo Koto was born of Nagari Koto Malintang, (2) How developed Nagari Koto Malintang inÂ  2005 to 2011, (3) How Redistricting Impact Nagari Koto Malintang in field Politi, Social, Cultural and Economic Nagari Koto Malintang on society. This research aims to: Explain How Background The emergence of Nagari Koto Malintang and see how the process of development and the impact after the holding of the division. The method used in this research is the study of history, with the following stages: first heuristic is a history of activity that collects data from various source documents, records and interviews. The second source of criticism is an activity to test the resources that have been collected through internal and external criticism. The third interpretation is that the data obtained from the field or library research. Assessing and cause and effect link between the incident occurred. The fourth Historiography is report presents the method describing logically and systematically to the data that is processed into the form of a scientific paper. These results indicate that: before the territory Nagari Koto Malintang bloomed so many problems that arise in terms of which is the centralized public services in Nagari Koto Gadang, too far from Nagari Koto Malintang, jorong Koto Gadang villages have less result than Koto Malintang and the absence of rules clear about the position and authority of the administrative villages process. After Nagari Koto Malintang area bloomed on February 25, 2005 many changes including progress in the economic, political and social culture in warehouses etc. It can be concluded after the establishment of this Nagari Koto Malintang the growing population of Nagari Koto Malintang yieding progress and activities of many social interactions generate many positive impact, in education, health and other social services.Â Key Word: Development Nagari Koto Malintang.